Facial responsiveness of psychopaths to the emotional expressions of others. - Janina Künecke; Andreas Mokros; Sally Olderbak; Oliver Wilhelm (PLoS ONE, 2018)
Psychopathic individuals show selfish, manipulative, and antisocial behavior in addition to emotional detachment and reduced empathy. Their empathic deficits are thought to be associated with a reduced responsiveness to emotional stimuli. Immediate facial muscle responses to the emotional expressions of others reflect the expressive part of emotional responsiveness and are positively related to trait empathy. Empirical evidence for reduced facial muscle responses in adult psychopathic individuals to the emotional expressions of others is rare. In the present study, 261 male criminal offenders and non-offenders categorized dynamically presented facial emotion expressions (angry, happy, sad, and neutral) during facial electromyography recording of their corrugator muscle activity. We replicated a measurement model of facial muscle activity, which controls for general facial responsiveness to face stimuli, and modeled three correlated emotion-specific factors (i.e., anger, happiness, and sadness) representing emotion specific activity. In a multi-group confirmatory factor analysis, we compared the means of the anger, happiness, and sadness latent factors between three groups: 1) non-offenders, 2) low, and 3) high psychopathic offenders. There were no significant mean differences between groups. Our results challenge current theories that focus on deficits in emotional responsiveness as leading to the development of psychopathy and encourage further theoretical development on deviant emotional processes in psychopathic individuals.